2015
DOI: 10.1007/s00277-015-2484-y
|View full text |Cite
|
Sign up to set email alerts
|

Lack of survival improvement with novel anti-myeloma agents for patients with multiple myeloma and central nervous system involvement: the Greek Myeloma Study Group experience

Abstract: Involvement of the central nervous system (CNS) is a rare complication of multiple myeloma (MM). Herein, we have described the incidence, characteristics, prognostic factors for post CNS-MM survival, and outcome of CNS-MM and explored the efficacy of novel agents (NA) (thalidomide, bortezomib, lenalidomide) in this setting. Between 2000 and 2013, 31 (0.9 %) out of 3408 newly diagnosed symptomatic MM patients, consecutively diagnosed and treated during the same period in 12 Greek centers, developed CNS-MM (M/F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…35,36 Retrospective studies highlight an extremely poor prognosis for CNS EMM with a median overall survival of ,6 months. [35][36][37][38][39] Any neurologic symptom presented by an MM patient should raise the possibility of the presence of CNS EMM. However, alternative diagnoses should be considered (eg, hypercalcemia, hyperviscosity, spinal cord compression, CNS infection, and peripheral neuropathy).…”
Section: Spmentioning
confidence: 99%
“…35,36 Retrospective studies highlight an extremely poor prognosis for CNS EMM with a median overall survival of ,6 months. [35][36][37][38][39] Any neurologic symptom presented by an MM patient should raise the possibility of the presence of CNS EMM. However, alternative diagnoses should be considered (eg, hypercalcemia, hyperviscosity, spinal cord compression, CNS infection, and peripheral neuropathy).…”
Section: Spmentioning
confidence: 99%
“…2 months). 15 By multivariable analysis, extramedullary lesions, prior to treatment with novel drugs, and high LDH levels at myeloma diagnosis were statistically independent predictors of post CNS-MM survival. These findings corroborate our observations that our patient with CNS relapse of PPCL had an extremely short-term outcome.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that 19% of post CNS-MM patients met the criteria for PPCL. 15 Furthermore, some of these PPCL patients developed isolated CNS relapse during systemic remission after auto-SCT. 8,9,15 In a prospective study by Royer et al, 2 PPCL patients experienced neuromeningeal relapse after autologous- and allo-SCT, respectively, and both patients soon died despite intrathecal chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations